Prediksi Potensi Cadangan Air Tanah Menggunakan Persamaan Darcy di Kecamatan Dramaga, Kabupaten Bogor - Pangestu, Pangestu; Waspodo, Roh Santoso Budi (Departemen Teknik Sipil dan Lingkungan IPB, 2019)
Groundwater needs will increase in accordance to area development. Groundwater has a limited quantity because it depends on the geometry and distribution of aquifer. The purpose of this study were to identify soil lithology and aquifer thickness, to determine soil hydraulic conductivity values and to predict potential groundwater reserves in Dramaga District . The processed data were data geoelectric with Schlumberger configuration, hydrogeological maps, and geological maps of Bogor. Aquifer thickness were obtained from the average yield of the aquifer thickness at the research location. Thickness of unconfined aquifer was 14,69 m and 17,77 m for confined aquifer. Aquifer had lithological layers of andesite, tuffaceous, sandstone, clay, and sand. The value of hydraulic conductivity was 2,5 m / day for unconfined aquifer and 2,04 m / day for confined aquifer. Using the Darcy equation groundwater reserves were estimated 241,29 m3 / day or 2,79 l / s for unconfined aquifers and 1291,19 m3 / day or 14,94 l / s for confined aquifers.Key words: aquifer, Darcy equation, geoelectric, groundwater reserves